Adsorption mechanism for tetracycline onto magnetic Fe3O4 nanoparticles: Adsorption isotherm and dynamic behavior, location of adsorption sites and interaction bonds. (January 2022) - Zhai, Wangjian; He, Junfeng; Han, Peng; Zeng, Min; Gao, Xingsen; He, Qinyu
Abstract: Fe3 O4 nanoparticles as a magnetic adsorbent were prepared and used to effectively remove tetracycline (TC) from neutral aqueous solution. Several characterizations show that the as-prepared Fe3 O4 nanoparticles possess a saturation magnetization of 79.4 emu/g, a specific surface area of 58.8 m 2 /g and an average particle size of 25 nm. Batch experiments were carried out to investigate the adsorption behavior and mechanisms. For a 100 mL TC solution with an initial concentration of 10 mg/L, the TC absorption reached adsorption-desorption equilibrium with a removal efficiency of 97.2% in 90 min. Adsorption kinetic and isotherm studies demonstrated that the adsorption process fits well with pseudo-second-order kinetics models. The Langmuir isotherm model was found to be more suitable than the Freundlich isotherm model for describing the adsorption equilibrium data. Adsorption between Fe3 O4 and TC is achieved by the formation of hydrogen bonds between the H atoms of the C–O(H) bonds located at the B or D ring of TC and the O atoms of Fe3 O4 . Furthermore, the hydrogen bonds formed at the octahedral site are stronger than those formed at the tetrahedral site. This new understanding provides an important reference and guidance for the design and modification of Fe3 O4 -based nanomaterials for TC removal. Highlights: Removal efficiency of tetracycline reached 97.2% in 90 min. Tetracycline are adsorbed on the Fe3 O4 surface by forming hydrogen bonds. Hydrogen bonds are formed between the H atoms of the C–O(H) bond located at the B or D ring of Tetracycline and the O atoms of Fe3 O4 . Hydrogen bonds formed at the octahedral site are stronger than those formed at the tetrahedral site.